How should a national curriculum for History be quality assured? The case of the South African Curriculum and Assessment Policy Statement (CAPS) (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
The South African Council for Quality Assurance in General and Further Education and Training, known as Umalusi, embarked on a project to quality assure the South African Curriculum and Assessment Policy Statement (CAPS) curriculum for schools (2011) in 2012. This article analysis the process in terms of the history curriculum and provides a commentary on universal principles for the quality assurance of national curricula in general. Six quality assurance measures are identified and discussed: comparison between the outgoing and the incoming curricula; entry- and exit-level requirements; internal comparison between Phases [Key Stages] of the curriculum; comparison of the history curriculum statement with statements for other curriculum subjects; current trends in history education; and comparison with history curricula in other countries. Conclusions are drawn for Umalusi and its practice, the CAPS curriculum itself, and the history curriculum.
Keywords: Curriculum; Quality assurance; Accreditation; Umalusi; CAPS; NCS; Intermediate phase; Senior phase; FET; historical knowledge; historical skills